2013
DOI: 10.5194/jsss-2-171-2013
|View full text |Cite
|
Sign up to set email alerts
|

Early forest fire detection using low-energy hydrogen sensors

Abstract: Abstract. Most huge forest fires start in partial combustion. In the beginning of a smouldering fire, emission of hydrogen in low concentration occurs. Therefore, hydrogen can be used to detect forest fires before open flames are visible and high temperatures are generated. We have developed a hydrogen sensor comprising of a metal/solid electrolyte/insulator/semiconductor (MEIS) structure which allows an economical production. Due to the low energy consumption, an autarkic working unit in the forest was establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In other words, CO can reach concentrations that affect the human body before the fire alarm is activated. It has also been reported that hydrogen, which is generated at the same time as CO, can be detected more quickly than CO in this type of incomplete combustion [3,5,6,11]. Given that hydrogen is lighter than air, hydrogen can easily be detected by placing a hydrogen sensor on the ceiling [5,6,11].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In other words, CO can reach concentrations that affect the human body before the fire alarm is activated. It has also been reported that hydrogen, which is generated at the same time as CO, can be detected more quickly than CO in this type of incomplete combustion [3,5,6,11]. Given that hydrogen is lighter than air, hydrogen can easily be detected by placing a hydrogen sensor on the ceiling [5,6,11].…”
Section: Introductionmentioning
confidence: 95%
“…Although very little hydrogen is produced by smoldering fires (on the order of ppm), by employing a highly sensitive hydrogen sensor, it is possible to detect the hydrogen produced by a smoldering fire [3,5,6,11]. However, to continuously monitor hydrogen gas, hydrogen sensors must operate with low power consumption.…”
Section: Introductionmentioning
confidence: 99%